STUDENTS’ PERCEPTIONS TOWARDS USING ICT IN SPEAKING SKILL DEVELOPMENT - Praysita Dondo; Paula Hampp; Rinny Rorimpandey (KOMPETENSI, 2022)
This research aims at describing students’ perceptions towards using information and communication technology in speaking skill development. The researchers use a qualitative research design with a non-experimental research. The population of this research is the students of EnglishEducationDepartment UNIMA and the sample is 30 respondents who experienced using ICT in their speaking skill development. The data are collected by using questionnaire as the research instrument. The result of this study indicates that students agreed that they can easily access English learning platforms with ICT and practice speaking. They experience positive use of ICT in practicing speaking and even develop their speaking skills because ICT helps students to recognize their mistakes, learn correct pronounciation, learn more vocabulary, and build a regular speaking practice.